Practice rehearsal pairs with dynamic video media: Improving students' kinematics graph interpretation skills - Luluk Hariroh; Arif Hidayat; Sutopo Sutopo; Endang Purwaningsih (Momentum: Physics Education Journal, 2024)
This study aims to examine the impact of Practice Rehearsal Pairs (PRPs) with Dynamic Video Media (DVM) on improving students' skills to interpret kinematics graphs in Physics subjects among junior high school students in Malang. This research is descriptive with a quantitative approach. Data collection was conducted through tests, observations with open questionnaires to three classes totaling 77 eighth-grade students in Malang City. Semi-structured interview participant selection was carried out to obtain detailed and in-depth answers from the students' perspectives. The instrument used to explore kinematics graph interpretation abilities consisted of 10 kinematics graph questions taken from The Test of Understanding Graphs in Kinematics (TUG-K). The research results show that eighth-grade junior high school students in Malang have a low ability to interpret kinematics graphs, with an average initial exploration ability score of 54.6. The difficulties experienced by students include reading graphs through slope/gradient, area under the graph, and direct graph reading. The PRPs learning model with DVM can improve the ability to interpret kinematics graphs of junior high school students. In the three experimental classes, there was an increase in initial exploration ability scores and final ability test scores. The non-parametric test results using the Wilcoxon Signed Rank Test show that all three classes have a Sig. (2-tailed) value of 0.000 < 0.05, thus it can be concluded that there is a significant difference between the initial and final abilities of students in the experimental classes before and after the implementation of PRPs and the use of DVM. This indicates that the PRPs learning model with DVM can improve the ability to interpret kinematics graphs of junior high school students.